Presidential Threshold in the 2024 Presidential Elections: Implications for the Benefits of Democracy in Indonesia - Umarwan Sutopo; Achmad Hasan Basri; Hilman Rosyidi (Faculty of Sharia UIN Kiai Ageng Muhammad Besari Ponorogo, 2024)
Elections are one of the Indonesian people's efforts to elect the best leaders as well as the embodiment of a democratic country. The Presidential Threshold (PT) that applies in the 2024 presidential election (Pilpres) is one of the things that has become a polemic in society. This can be seen in several judicial review processes by the public and groups requesting the abolition of the threshold. With normative research and conceptual and legislative approaches relating to elections in general and presidential elections in particular, this research questions its benefits. The benefit in question is the benefit that returns to the community in particular and the government system that is formed. Through literature study and qualitative analysis, the results showed that the existence of PT contradicts the wrongful benefits and á¸arÅ«rÄ« in the nation's life and democracy. This means the people are limited in choosing presidential and vice-presidential candidates who truly suit their wishes. The nation's best sons and daughters are limited in their rights to nominate themselves as leaders because of the PT. Furthermore, the ruling party has a tremendous opportunity to control the presidential system, both at the legislative and executive levels, and this is undoubtedly contrary to the benefit itself.